Tinjauan Yuridis Peran Pelopor Brimob Polda Sumut dalam Penegakan Hukum terhadap Kejahatan Berbasis Kekerasan (Studi Kasus Brimob Polda Sumatera Utara): Studi Kasus Brimob Polda Sumatera Utara - Dedy Kurniawan; Yeltriana Yeltriana (Lembaga Pengabdian Masyarakat Universitas Ichsan Gorontalo, 2025)
Violent crimes such as armed robbery, terrorism, riots, and hostage-taking pose serious threats to public safety and order. In this context, the Brimob Pelopor Unit of the North Sumatra Regional Police plays a strategic role as a paramilitary police force trained to handle high-intensity threats. This research is driven by the urgency to examine the extent to which Brimob’s role is carried out within the framework of criminal law and the principles of fair, professional, and proportional law enforcement. The aim of this study is to analyze the legal foundations underlying the involvement of the Brimob Pelopor Unit in handling violent crimes, identify operational and institutional obstacles faced, and evaluate the strategies implemented within the context of law enforcement. The method employed is a descriptive qualitative approach, using data collection techniques such as interviews, observations, and document studies. The findings indicate that the Brimob Pelopor Unit of North Sumatra actively participates in operations against armed crime, riot control, and securing vital objects, based on clear legal provisions such as Law No. 2 of 2002 and police regulations regarding the use of force. Key challenges include limited personnel, tactical equipment shortages, bureaucratic delays, and public pressure concerning human rights issues. Nevertheless, various reinforcement strategies are being pursued through intensive training, inter-agency collaboration, and a humanistic approach to community engagement. This study concludes that Brimob’s role is crucial in Indonesia’s law enforcement system, though continuous reform is required to maintain professionalism and legal legitimacy amid complex national security challenges.